2017
DOI: 10.4094/chnr.2017.23.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Clinical Practice Burnout in Student Nurses

Abstract: Purpose:The purpose of this study was to explore perception of the clinical learning environment, resilience and perfectionism in relation to practice burnout and to identify factors influencing practice burnout in student nurses. Methods: A descriptive correlational study was conducted. The participants were 313 student nurses from three universities in B and U city. Data were analyzed using t-test, ANOVA, Pearson correlation coefficient, Scheffés test and multiple regression analysis. Results: Mean score for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…For example, “I feel tired from my clinical practice,” “I'm not interested in clinical practice at present,” and” I don't have a passion for clinical practice right now.” The higher the score, the higher the clinical practice burnout. The reliability of the tool in a previous study (Cho & Kang, 2017) that measured “clinical practice burnout” using the same tool was Cronbach's alpha = 0.880. The reliability of the tool for clinical practice burnout in this study, as measured by Cronbach's alpha was 0.910.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, “I feel tired from my clinical practice,” “I'm not interested in clinical practice at present,” and” I don't have a passion for clinical practice right now.” The higher the score, the higher the clinical practice burnout. The reliability of the tool in a previous study (Cho & Kang, 2017) that measured “clinical practice burnout” using the same tool was Cronbach's alpha = 0.880. The reliability of the tool for clinical practice burnout in this study, as measured by Cronbach's alpha was 0.910.…”
Section: Methodsmentioning
confidence: 90%
“…The higher the score, the higher the clinical practice burnout. The reliability of the tool in a previous study (Cho & Kang, 2017) that measured "clinical practice burnout" using the same tool was Cronbach's alpha = 0.880. The reliability of the tool for clinical practice burnout in this study, as measured by Cronbach's alpha was 0.910.…”
Section: Clinical Practice Burnoutmentioning
confidence: 90%
“…The purpose and importance of research In this study, the relationship between perfectionism and burnout was investigated in the sample of marble sector employees. In the literature, the relationship between perfectionist personality trait and burnout has been explored on different sample groups, including especially athletes (Appleton et al2009;Hill et al, 2010), teachers (Stoeber and Rennert, 2008;Childs and Stoeber 2012, p.347), bank employees (Kakırman and Birsel, 2015), students (Cho and Kang, 2017;Zhang et al 2007;Çam et al 2014, p. 312), nurses (Balevre et al 2012;Çam et al 2014), doctors (Badawy and Mohamad, 2015, p. 7), executives (Fry, 1995cited by D'Souza et al 2011, academicians (Sakal and Yıldız, 2017, p. 38). However, there is very little work done on a sectoral basis, especially blue-collar workers.…”
Section: Methodsmentioning
confidence: 99%
“…For nurses to be able to counsel a guardian on ADs, they should not just have heard of ADs but also have experience with the completion of ADs [ 12 ]. Previous studies have shown that the experience level of nurses regarding the completion of ADs varies according to the clinical environment, and although the role of nurses depends on where they work, nurses typically receive insufficient practice completing ADs even though nurses in Korea are advocates of patients [ 13 ]. One previous study found that 50.4% of ICU nurses had never heard of ADs [ 14 ], and another showed that general ward nurses also had little experience with ADs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses at long-term care hospitals should provide sufficient information about diseases and prognoses through communication with patients in the clinical field, act as advocates, and have a positive attitude toward ADs in order to complete them properly [ 16 ]. Nurses’ attitudes toward ADs are more positive when their perception of death is positive [ 13 ], if they were older and worked for a longer period of time at the hospital [ 16 ], and if they had received training regarding ADs [ 13 , 15 ]. In addition, significant differences were observed in nurses’ attitudes toward ADs according to age, religion [ 17 ], and subjective health conditions [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%